11, 13 and 15 Charles Street, January 14, 1973 - Waid, C. Franklin (Tufts Archival Research Center, 2005)
Street-level view east of 11, 13 and 15 Charles Street, located between Beacon Street to the south and Branch Street to the north. Signage adorns the facades of the buildings which face west-southwest, and parking meters line the sidewalk along the east side of Charles Street. 7 3/8 x 9 3/8, 7 7/8 x 9 7/8 overall Photographs